ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN KANTOR AKUNTAN PUBLIK SECARA SUKARELA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yohana, Rinna; Lindrawati, Lindrawati; Lasdi, Lodovicus (Widya Mandala Surabaya Catholic University, 2013)
The increased need of public accounting service, makes numbers of public accountant firm increasing too. The in-creased numbers of public accountant firm, may result competition between public accountant firms. On the other hand, many choices of public accountant firm can makes company perform voluntary auditor changes. Because that, the purpose of this research is to analyze the effect of management changes, auditor reputation, financial distress, auditor’s opinion in the last year, and profitability to voluntary auditor changes. Quantitative research design using hypothesis. The research data form of panel data. Types of data used are quantitative data form of financial statements and qualitative data such as name of public accountant firms, auditor's opinion, and name of president director. Research population is manufactur-ing company listed on the Indonesia Stock Exchange in 2009-2011, with sample of 76 companies were selected by pur-posive sampling technique. The technique of data analysis using logistic regression. The results showed that the auditor's reputation had a negative effect on voluntary KAP turnover and profitability had a positive effect on voluntary KAP turnover. Conversely, changes in management, financial difficulties, and the auditor's opinion of the previous year did not affect voluntary KAP changes.